Single versus multiple arterial grafting in diabetic patients at 10 years: the Arterial Revascularization Trial. (14th June 2022) - Taggart, David P; Audisio, Katia; Gerry, Stephen; Robinson, N Bryce; Rahouma, Mohamed; Soletti, Giovanni Jr; Cancelli, Gianmarco; Benedetto, Umberto; Lees, Belinda; Gray, Alastair; Stefil, Maria; Flather, Marcus; et al.
Abstract: Aims: To evaluate the impact of multiple arterial grafting (MAG) vs. single arterial grafting (SAG) in a post hoc analysis of 10-year outcomes in patients with diabetes mellitus (DM) from the Arterial Revascularization Trial (ART). Methods and results: The primary endpoint was all-cause mortality and the secondary endpoint was a composite of major adverse cardiac events (MACE) at 10-year follow-up. Patients were stratified by diabetes status (non-DM and DM) and grafting strategy (MAG vs. SAG). A total of 3020 patients were included in the analysis; 716 (23.7%) had DM. Overall, 55.8% non-DM patients received MAG and 44.2% received SAG, while 56.6% DM patients received MAG and 43.4% received SAG. The use of MAG compared with SAG was associated with lower 10-year mortality for both non-DM [17.7 vs. 21.0%, adjusted hazard ratio (HR) 0.87, 95% confidence interval (CI) 0.72–1.06] and DM patients (21.5 vs. 29.9%, adjusted HR 0.65, 95% CI 0.48–0.89; P for interaction = 0.12). For both groups, the rate of 10-year MACE was also lower for MAG vs. SAG. Overall, deep sternal wound infections (DSWIs) were uncommon but more frequent in the MAG vs. SAG group in both non-DM (3.3 vs. 2.1%) and DM patients (7.9 vs. 4.8%). The highest rates of DSWI were in insulin-treated patients receiving MAG (9.6 vs. 6.3%, when compared with SAG). Conclusion: In this post hoc analysis of the ART, MAG was associated with substantially lower mortality rates at 10 years after coronary artery bypass grafting in patients with DM. Patients with DM receiving MAG had a higher incidence of DSWI, especially if insulin dependent. Structured Graphical Abstract: Structured Graphical Abstract 10 year survival in non-diabetic and diabetic patients with single or multiple arterial grafts.